Anoctamin 9/TMEM16J is a cation channel activated by cAMP/PKA signal. (May 2018) - Kim, Hyungsup; Kim, Hyesu; Lee, Jesun; Lee, Byeongjun; Kim, Hee-Ryang; Jung, Jooyoung; Lee, Mi-Ock; Oh, Uhtaek
Graphical abstract: Highlights: ANO9/TMEM16J is activated by cAMP/PKA signal. Unlike Anoctamin 1 or 2, a Ca 2+ -activated Clchannel family, ANO9 is a cation channel. Colon cells expressed high levels of Ano9 and showed cAMP-dependent currents. Abstract: Anoctamins (ANOs) are multifunctional membrane proteins that consist of 10 homologs. ANO1 (TMEM16A) and ANO2 (TMEM16B) are anion channels activated by intracellular calcium that meditate numerous physiological functions. ANO6 is a scramblase that redistributes phospholipids across the cell membrane. The other homologs are not well characterized. We found ANO9/TMEM16J is a cation channel activated by a cAMP-dependent protein kinase A (PKA). Intracellular cAMP-activated robust currents in whole cells expressing ANO9, which were inhibited by a PKA blocker. A cholera toxin that persistently stimulated adenylate cyclase activated ANO9 as did the application of PKA. The cAMP-induced ANO9 currents were permeable to cations. The cAMP-dependent ANO9 currents were augmented by intracellular Ca 2+ . Ano9 transcripts were predominant in the intestines. Human intestinal SW480 cells expressed high levels of Ano9 transcripts and showed PKA inhibitor-reversible cAMP-dependent currents. We conclude that ANO9 is a cation channel activated by a cAMP/PKA pathway and could play a role in intestine function.